Pengaruh Gaya Mengajar Latihan Terhadap Keterampilan Menggiring Bola Dengan Kaki Bagian Dalam Pada Permainan Sepak Bola Pada peserta didik SMP Negeri 2 Kumelembuai - Keren Kumayas; Tony Pandeleke; Jan Lengkong (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2025)
The results of observations in the field show that Class VIII students of SMP Negeri 2 Kumelembuai do not master the technique of dribbling with the inside of the foot when playing soccer. One of the other problems found is that the learning method used to teach players to dribble with the inside foot in soccer games is still conventional. There is no known learning method that can improve dribbling skills with the inside foot in soccer games or whether students have the ability to dribble with the inside foot in soccer games. This research uses an experimental method. This study involved 30 male students from Class VIII of SMP Negeri 2 Kumelembuai. Furthermore, the sample was divided into two groups: the experimental group and the control group, each of which had 15 people. The instrument used is a test of dribbling skills with the inside foot in soccer games. The data analysis technique used is the t-test statistical analysis technique, before the t-test is carried out, it first begins with testing the analysis requirements, namely the data normality test and the variance homogeneity test. Based on the results of hypothesis testing using the t test statistic, the results of this study can be concluded that there is an effect of the application of the practice style on the ability to dribble using the inside foot in the soccer game of SMP Negeri 2 Kumelembuai students.